The intrinsic and instrumental value of money and resource management for people's wellbeing in rural Kenya - Silvia Storchi (University of Bath, Centre for Development Studies (CDS), 2017)
This report uses a theoretical framework based on Sen's Capability Approach to suggest financial capability should be understood as a set of reachable financial opportunities, which individuals have reason to value to achieve their wellbeing goals. From this perspective, financial inclusion can be evaluated according to its ability to facilitate poor and excluded individuals to better pursue their wellbeing goals. The empirical contribution of this report shows that formal bank accounts, while instrumentally valuable as means for savings, do not fit with a local mode of development based on mutual support and "upliftment". By contrast informal financial strategies are more aligned with local social norms and moral values. They are therefore intrinsically better at contributing to people's quality of life. By considering the role of non-economic value drivers, this report invites the financial sector to deepen its understanding of how and why services' are adopted and used. It challenges the financial sector to align its financial inclusion proposition with such a broad set of drivers in mind.
Keywords: 330; Financial Inclusion; Wellbeing; Capability Approach; Kenya